Separation of crude oil emulsion via microwave heating technology - Siti Nuurul Huda, Mohammad Azmin (2009)
Emulsion is a mixture of two immiscible substances which is divided into two types of emulsions either a water-in-oil emulsion or oil-in-water emulsion. Emulsion is unstable. For economic purpose, pipeline consideration and for efficient refinery operations, the produced crude oil must dewatered and necessary to separate the water completely from the crude oils before transporting them. In this study, two types of crude oil with three volume ratio of water-oil 50-50%, 30-70% and 20-80%(w/o) were used and they were added by four different types of surfactants (Triton-X-100, Tween 80, Span 80 and SDDS) in different concentration which are 0.5%, 2.5% and 4.5%. Then this water-oil volume ratio and surfactant was heating by using microwave at two different powers which are 180 watt and 720 watt. The findings from this study are microwave heating technology can be an alternative method for demulsification for water-oil emulsion. Microwave heating technology can be use for more effective, time and energy saving and low cost method for demulsification process compare to the conventional methods.